PERANAN INFOMASI AKUNTANSI TERHADAP KEBERHASILAN UMKM DI KOTA LANGSA - Mastura, Mastura; Sumarni, Mutia; Eliza, Zulfa (IAIN Langsa, 2019)
Among the leading Micro, Small and Medium Enterprises in Langsa are shrimp paste, soy sauce and touco, but it is unfortunate, those Enterprises have not paid attention to the importance of accounting knowledge and have not fully used accounting information in conducting their businesses. Accounting information is very importance to the success of Micro, Small and Medium Enterprises in Langsa City and whether accounting information can increase the success of Micro, Small and Medium Enterprises in Langsa City. This study is a qualitative study whose research subjects are shrimp paste, soy sauce and touco businesses in Langsa City. The results showed that accounting information plays an important role in the success of Micro, Small and Medium Enterprises in Langsa City and can increase the success of Micro, Small and Medium Enterprises in Langsa City